Within session practice effects in patients referred for suspected dementia - Duff, Kevin (2012)
BACKGROUND: Practice effects are improvements in cognitive test performance associated with repeated administrations of same or similar measures and are traditionally seen as error variance. However, there is growing evidence that practice effects provide clinically useful information. METHODS: Within session practice effects (WISPE) across 2 hours were collected on sixty-one non-consecutive patients referred for suspected dementia and compared to the Mini Mental Status Examination (MMSE), a screening measure of dementia severity. RESULTS: In all patients, WISPE on two cognitive measures were significantly correlated with MMSE, even after controlling for baseline cognitive scores (partial r=0.47, p<0.001; partial r=0.26, p=0.046). In patients diagnosed with probable Alzheimer’s disease, the trend was even stronger (partial r=0.72, p<0.01; partial r=0.58, p=0.046). In both groups, lower WISPE were associated with lower MMSE scores (i.e., greater dementia severity), even after controlling for initial cognitive scores. CONCLUSION: If future research validates these findings with longitudinal studies, then WISPE may have important clinical applications in dementia evaluations.